Assisting the Transition from Workfare to Work : A Randomized Experiment - Galasso, Emanuela; Ravallion, Martin; Salvia, Agustin (World Bank, Washington, DC, 2014)
Randomly sampled workfare participants in a welfare-dependent region of Argentina were given a voucher that entitled an employer to a sizable wage subsidy. A second sample also received the option of skill training, while a third sample formed the control group. The authors analyze the effects of this scheme on participants' employment and income, using double-difference and instrumental-variables methods to deal with potential experimental biases, including selective compliance with the randomized assignment. The authors find that compared with the control group, voucher recipients had a significantly higher probability of employment, though their current incomes were no higher. The impact was largely confined to women and younger workers. Labor supply effects appear to have been important. However, training had no significant impact. The experiment was cost-effective in reducing the government's welfare spending, since take-up of the subsidy by employers was low.